Cancer immunology - Elliott, Tim (Henry Stewart Talks, 2021)
Function and regulation of cell division, The hallmarks of cancer, Immune surveillance, Evidence of anti-tumour T-cell responses, T cell recognition of cancer cells, Evasion of tumour immunity, Immune escape, Immune suppression
Reviewed at 2025/01/29